Proceedings of the Greater Mekong Subregion urban development and planning training program. (Metro Manila, Philippines Asian Development Bank, 2017)
Almost half of Asias residents live in urban areas where the population is increasing by about 44 million each year. This report summarizes the 5 day training program on the urban development and planning experience of the PRC. It was held 1115 May 2015 in Yunnan Province, the PRC, for the benefit of key officials of the Greater Mekong Subregion countries Cambodia, the PRC, the Lao Peoples Democratic Republic, Myanmar, Thailand, and Viet Nam. Discover the challenges arising from the speed and scale of the PRCs urban development in the areas of environmental degradation, inadequacy of social services, and inequality in standards of living. Find out how the PRCs urban development experience gave birth to valuable lessons which can be adopted by the Greater Mekong Subregion countries.
Keywords: Economic assistance -- Greater Mekong Subregion -- Evaluation; Technical assistance -- Greater Mekong Subregion; Electronic books